Pengembangan Modul IPAS pada Materi Fotosintesis (Studi Morfologi pada Tanaman Kopi Arabika Ijen Bondowoso) untuk Mengoptimalkan Kemampuan Literasi Sains Siswa Sekolah Dasar - Maulia Eka Nur Ardillah (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
The IPAS module on photosynthesis is a teaching resource that integrates local natural resources as a means to optimize elementary school students’ science literacy skills. This module connects IPAS content with real-world conditions in the surrounding environment, particularly in the photosynthesis unit, which was developed through a morphological study of Arabica coffee plants from Ijen Bondowoso, providing students with a more meaningful and contextual learning experience. This study aims to determine the validity, practicality, and effectiveness of the module in optimizing the science literacy skills of 4th grade elementary school students. This study used the Research and Development method with Thiagarajan’s 4D development model. The research subjects consisted of 24 students from Class 4B at UPTD SPF SD Negeri Dabasah 3 Bondowoso. The results indicate that the module achieved a validity score of 84.8%, classified as “highly valid,” in the module validity test and a practicality score of 89.5%, classified as “highly practical” in the students responses. The module’s effectiveness was demonstrated by an increase in the average pretest score from 47.2 to 83.7 on the posttest, resulting in an N-gain of 0.69, which falls within the “effective” category. Based on these results, the module on photosynthesis with a morphological study of Ijen Bondowoso Arabica coffee plants is proven to be valid, practical, and effective, making it suitable for use as contextual teaching material to optimize elementary school students’ science literacy skills. Keywords: IPAS module; photosynthesis; arabica coffee morphology; science literacy; elementary school students
Finalisasi_Maya_19 Juni 2026
Keywords: Literasi Sains Tanaman Kopi Arabika Ijen Bondowoso Sekolah Dasar